Comparative bioclimatic approach for comfort and passive heating and cooling strategies in Algeria. (15th August 2019) - Semahi, Samir; Zemmouri, Noureddine; Singh, Manoj Kumar; Attia, Shady
Abstract: The energy consumption and thermal comfort in buildings are heavily affected by weather conditions. Therefore, the aim of this paper is to analyze the bioclimatic potential of Algerian climate zones. This analysis was made based on eight representative locations using recent weather datasets (2003–2017). The thermal comfort and passive design potential analysis were based on a psychometric chart applying the adaptive comfort model ASHRAE 55–2017. In addition, an evaluation of the bioclimatic potential was conducted using simulations of a monitored and calibrated residential building model in Algeria using EnergyPlus. The building model has been tested in eight previously selected locations. The heating and cooling energy load results were calculated for each climatic zone and compared. The results allow architects and urban planners to better understand the climate and provide practical design guidance. Highlights: The bioclimatic potential of the six climate zones of Algeria was calculated. A monitoring-based simulation model was created and calibrated. A strong correlation exists between the bioclimatic potential and performance. The average percentage of discomfort hours in Algerian households is between 58% and 75%. Our study confirms the need for a new bioclimatic zoning map for Algeria.